Effectiveness of Health Education in Increasing Knowledge and Attitude Towards Free Sex in Medan - Nasution, Siti Saidah; Erniyati, Erniyati; Hariati, Hariati (Jurnal Keperawatan Soedirman, 2019)
Adolescence is an unstable period which often makes teenagers fall into free sex. Free sex generally occurs not only because of adolescent’s desire or willingness, but also by the influence of environment and the insufficient and incorrect health information. This research was part of community service with quantitative quasi-experimental research type. The sample in this study was 300 teenagers in the city of Medan which then divided into intervention group (n=150) and control group (n=150). The intervention was health education about reproduction and sexual development in adolescents by involving counseling teachers, and the establishment of reproductive and sexual health counseling team in school. Statistical test was performed with Mann-Whitney. The results showed that health education was effective in increasing knowledge (p = 0,000) and attitudes (p =0,000) of students towards free sex behavior in Medan. Adolescent’s knowledge and attitudes toward sexual behavior can be improved through counseling and education. Health workers must be able to optimize their role in providing health education and counseling especially about the adolescent’s sexual development by involving the role of family and school.